Peran Pemimpin dalam Mengatasi Konflik dan Stres di Lembaga Pendidikan Islam - Sulistyorini, Sulistyorini (Taallum: Jurnal Pendidikan Islam, 2017)
One of the most serious and frequent problems that afflict individuals and members of the organization is the issue of conflict and stress. No exception in Islamic educational institutions, there must be turmoil or conflict, both individual conflict and group conflict. Because humans as social beings always be associated with fellow human beings. In addition, problems often occur in life sometimes make the individual feel burdened and become stressed. Stress is a difficult thing to avoid, but that does not mean it cannot be overcome. Not all principals have the ability to resolve conflicts and stress well, even without sufficient experience to be missteps, and instead engage in conflicts, or worse, precisely the stressed principal facing the problem at the institution his leads.